3D Concrete Printing with Industrial Waste: Effects of GGBS and Spent Catalyst on Fresh and Hardened Properties - Noorwirdawati Ali, (International Journal of Integrated Engineering, 2025)
3D concrete printing (3DCP) is a revolutionary technology in construction that deposits concrete layers in a controlled way, reducing formwork, labour, and material waste. However, its heavy reliance on Portland cement and natural sand raises sustainability and performance challenges. This study determines the incorporation of Ground Granulated Blast Furnace Slag (GGBS) and spent catalyst (SC)—two industrial by-products—as partial replacements for cement (20–40% of GGBS) and sand (10–20% of SC) in 3DCP mixtures. The objective is to assess how these substitutions affect fresh properties (flowability, extrudability, buildability) and hardened performance (compressive and flexural strength at 7 and 28 days). Sixteen mix designs were cast with a water-to-cement ratio of 0.5 and 0.5% superplasticiser. Fresh-state tests included flow table measurements, manual extrusion through a 15 mm × 40 mm nozzle, and five-layer stacking trials. 100 × 100 × 100 mm cubes and 100 × 100 × 400 mm prisms were used to assess the hardened properties. Results indicate that GGBS enhances flowability and long-term strength, while SC accelerates early strength gain; all mixes exhibited acceptable printability. The optimum mix—30% GGBS and 20% SC—achieved the highest 28-day compressive strength (50.61 MPa) and flexural strength (6.73 MPa). These findings demonstrate that GGBS and SC are viable sustainable alternatives in 3DCP, improving environmental impact and structural performance without compromising printability.